The nanoscopic principles of capacitive ion sensing interfaces - Bueno, Paulo R. [UNESP]; Hein, Robert; Santos, Adriano [UNESP]; Davis, Jason J. (Royal Society of Chemistry (RSC), 2020)
Herein we discuss the operational principles of molecular interfaces that specifically recruit ions from an electrolyte solution and report this in a reagentless capacitive manner. At low ionic occupancy the response of the interface obeys a Debye-type phenomenon akin to classic image charge effects. At higher levels of occupancy, the response follows Thomas-Fermi screening and, significantly, is dependent on the electronic structure of the mesoscopic ion-receptor host-guest ensemble.